TRACE METAL PROFILES IN THE VARVED SEDIMENT OF AN ARCTIC LAKE - Outridge P.M.; Percival J.B.; McNeely R.; Stern G.A.; Lockhart W.L.; Hamilton P.B. (My University, 2005)
Varved (annually-laminated) sediments offer a rare and physically undisturbed archive of past trace metal deposition and limnological conditions. Here, a high-resolution 1,300 year record of metal accumulation is presented from a varved lake sediment on Devon Island in the Canadian High Arctic. Down-core concentration profiles of Cd, Cu and Zn were positively correlated (P < 0.01) with organic C (Cd, Zn) or with leachable Fe (Cu), while distinct sub-surface peaks of these metals coincided with those of Fe, S and other redox-sensitive elements such as Co, Cr and U. The fluxes of these metals since 1854 were correlated with elements such as Ca, Al and La (P < 0.001) which are predominantly of local geological origin. Furthermore, the Cd, Cu and Zn patterns did not match concurrent records in Greenland Summit ice over the last century, nor global industrial emission histories. These facts suggest that inputs from local geological sources, coupled with some degree of post-depositional mobility or association with organic matter inputs, explain the metals’ sedimentary profiles, which were apparently not affected by long-range atmospheric metal pollution. Mercury concentrations were strongly correlated with total diatom abundance over the last 400 yrs, especially during the 20th Century when a two-fold increase in Hg concentrations and a four order-of-magnitude increase in diatoms occurred in tandem. Since 1854, 81% of the variation in Hg flux was associated with diatom and Ca fluxes. A similar correspondence between Hg and diatoms was found in a second lake nearby, confirming that the relationship was not unique to the main study lake. Recent Hg increases in Arctic and sub-Arctic lakes have been attributed to global anthropogenic Hg emissions. We propose an alternative hypothesis for High Arctic lakes: the recent Hg increases may be partly or entirely the product of elevated rates of Hg scavenging from the water column caused by markedly greater algal productivity, which in turn was driven by accelerating climate warming during the 20th Century. Given the important environmental assessment and policy implications if the alternative hypothesis is true, the possible effects of climate warming on sedimentary Hg fluxes in this region deserve further study.
Keywords: sediments; trace metal